Transfer Pricing: Techniques and Uses (Book). - Burns, Thomas J.; Lin, W. Thomas (The Accounting Review, 1981)
Reviews the book "Transfer Pricing: Techniques and Uses," by Ralph L. Benke and James Don Edwards.